The effect of zinc complex of N-isopropenylimidazole on the morphological characteristics of gum tissues in experimental endodontic-periodontal lesions in rats Authors - Pavel A. Galenko-Yaroshevsky; Aleksandr А. Slavinskiy; Sergey S. Todorov; Viktor L. Popkov; Olga V. Shelemekh; Svetlana A. Lebedeva; Andrey V. Zadorozhniy; Anait V. Zelenskaya; Lusine O. Alukhanyan; Irina B. Nektarevskaya; Natalia D. Bunyatyan; Aleksandr А. Verevkin (Belgorod National Research University, 2023)
Introduction: Combined inflammatory and destructive processes affecting the dental pulp and tissues of the periodontal complex are among the most problem diseases of the dental system. Current therapy with use of available pharmacological agents does not always allow achieving the expected positive result. In addition, often the lack of information about morphological processes in the tissues of the dental system, in particular the gums, with endodontic-periodontal lesion (EPL) limits the ability of dentists to carry out targeted pharmacotherapy with both traditional and, in particular, new medications. The aim of the study was to evaluate the morphological characteristics of gum tissues in a therapeutic context of N-isopropenylimidazole zinc complex derivative in experimental endodontic-periodontal lesion in rats. Materials and Methods: A simulation of EPL in rats was performed in two ways: simultaneous induction of acute periodontitis and parodontitis by pulp extraction and natural infection of the pulp cavity, as well as by ligation of the necks of lower incisors. The research protocols included 5 groups of animals: 1st - intact group (control-1); 2nd - animals with simulated EPL (control-2); 3rd - animals with simulated EPL and treated with Metrogyl Denta® gel (M-D); 4th - animals with simulated EPL and treated with N-isopropenylimidazole zinc complex derivative gel under the laboratory code Pilim-1; and 5th - animals with simulated EPL and treated with the combination of M-D + Pilim-1. The gum of the lower incisors was taken for morphological studies. Slides were stained with hematoxylin and eosin. Computer morphometry was performed using the ImageJ software. Results and Discussion: The substances M-D, Pilim-1 and, especially, the combination of M-D+Pilim-1 (against the background of chlorhexidine bigluconate used as oral rinse) for 14 days in rats with simulated EPL cause a significant improvement of the morphological structure of the gum with minimal residual dystrophy and sclerosis. The combination M-D + Pilim-1 led to a 1.3-time increase in epithelial thickness, and a 1.5-time decrease in acanthosis depth in comparison with M-D, while the number of capillaries and their diameter had no significant differences. Compared with Pilim-1, the epithelial thickness increased 1.5 times, and the acanthosis depth and the number of capillaries decreased 1.6 and 1.4 times, respectively, whereas the diameter of the capillaries did not change significantly. The pronounced protective effect of the combination M-D + Pilim-1 on the morphological structure of the gingival mucosa of rats with simulated EPL may be associated with antimicrobial, anti-inflammatory, regenerating, angioprotective and antioxidant properties of both M-D and Pilim-1 separately, and, possibly to a greater extent, of the combination M-D + Pilim-1. Conclusion: The substances M-D, Pilim-1 and, especially, the combination M-D + Pilim-1 (against the background of chlorhexidine bigluconate used as oral rinse) for 14 days in rats with simulated EPL have a protective effect on the epithelial structure and the connective tissue of the proper mucous plate, manifested in active normalization of pathological changes and significant restoration of their organotypic structure.